COMICS AS EDUCATIONAL TOOLS IN TEACHING ENGLISH GRAMMAR, LEXIS AND COMMUNICATION SKILLS - Sedliarova, Olga; Soloveva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The paper claims comics to be efficient multimodal tools in teaching students of English not only grammar and vocabulary but also some communication skills, social and language norms of conducting a conversation. Being entertaining and having the multimodal potential that results in a strong effect on the recipients’ responsiveness, comics highly motivate students to integrate in education process and make learning fun for teachers and children alike.The authors aim at presenting an algorithm of teaching English and conversation skills by means of comics design teaching  passing through the following stages: introducing the communicative situation, learning cultural data (linguistic and extralinguistic) and a conversation pattern (social rules for opening, developing and closing a conversation), imitating the conversation, working with grammar patterns and speech clichés, reproducing the conversation following the pictures, and, finally, acting it out. Comics vividly demonstrate facial expressions and gestures of the characters that are crucial in communicating certain ideas in a multisemiotic way either accompanying speech or performing on their own.The authors present the results of the experimental teaching to nine/ ten-year old children in a secondary school in Russia which prove comics to be functional, well-structured tools for acquiring grammar, lexis and communication skills by young learners of English.